The role of hepatitis E virus infection in adult Americans with acute liver failure. Issue 6 (23rd June 2016) - Fontana, Robert John; Engle, Ronald E.; Scaglione, Steven; Araya, Victor; Shaikh, Obaid; Tillman, Holly; Attar, Nahid; Purcell, Robert H.; Lee, William M.; ,
Abstract : Acute hepatitis E virus (HEV) infection is a leading cause of acute liver failure (ALF) in many developing countries, yet rarely identified in Western countries. Given that antibody testing for HEV infection is not routinely obtained, we hypothesized that HEV‐related ALF might be present and unrecognized in North American ALF patients. Serum samples of 681 adults enrolled in the U.S. Acute Liver Failure Study Group were tested for anti‐HEV immunoglobulin (Ig) M and anti‐HEV IgG levels. Subjects with a detectable anti‐HEV IgM also underwent testing for HEV RNA. Mean patient age was 41.8 years, 32.9% were male, and ALF etiologies included acetaminophen (APAP) hepatotoxicity (29%), indeterminate ALF (23%), idiosyncratic drug‐induced liver injury DILI (22%), acute hepatitis B virus infection (12%), autoimmune hepatitis (12%), and pregnancy‐related ALF (2%). Three men ages 36, 39, and 70 demonstrated repeatedly detectable anti‐HEV IgM, but all were HEV‐RNA negative and had other putative diagnoses. The latter 2 subjects died within 3 and 11 days of enrollment whereas the 36‐year‐old underwent emergency liver transplantation on study day 2. At admission, 294 (43.4%) of the ALF patients were anti‐HEV IgG positive with the seroprevalence being highest in those from the Midwest (50%) and lowest in those from the Southeast (28%). Anti‐HEV IgG + subjects were significantly older, less likely to have APAP overdose, and had a lower overall 3‐week survival compared to anti‐HEV IgG ‐ subjects (63% vs. 70%; P = 0.018). Conclusion : Acute HEV infection is very rare in adult Americans with ALF (i.e., 0.4%) and could not be implicated in any indeterminate, autoimmune, or pregnancy‐related ALF cases. Past exposure to HEV with detectable anti‐HEV IgG was significantly more common in the ALF patients compared to the general U.S. population. (Hepatology 2016;64:1870‐1880)